2009
DOI: 10.1108/17538270910992773
|View full text |Cite
|
Sign up to set email alerts
|

Considering client‐driven sustainability in residential housing

Abstract: PurposeEnergy emissions from the new houses being built over recent years have increased rather than declined since the implementation of the current government rating system. This is despite evidence of Australians' growing concern about climate change. This paper seeks to compare the demographics, attitudes and knowledge of people considering building a new home with the factors that would motivate them to adopt a more sustainable home.Design/methodology/approachThe empirical data from a survey of 32 people … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…As a result, the influence of friends and family may not be one of the judging criteria of owning these homes. In fact, Raisbeck and Wardlaw (2009) showed that other people's opinions are not a major factor to persuade home builders to construct a sustainable home in Australia.…”
Section: Structural Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, the influence of friends and family may not be one of the judging criteria of owning these homes. In fact, Raisbeck and Wardlaw (2009) showed that other people's opinions are not a major factor to persuade home builders to construct a sustainable home in Australia.…”
Section: Structural Modelmentioning
confidence: 99%
“…Furthermore, others have argued that attitude and self identity are interrelated. There are studies which found that individuals who view themselves concerned with environmental issues are more likely to have favorable attitudes towards practicing environmentally responsible behavior (Raisbeck & Wardlaw, 2009;Smith & Paladina, 2010;Pino et al, 2012).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The ability of energy rating systems to accurately reflect the capability of a home's energy performance has been, and continues to be, of immense interest to researchers. A growing appreciation of the importance of occupant behaviour has been observed (Hannah, 2011;Horne and Hayles, 2008;Joelsson and Gustavsson, 2008;Kordjamshidi and King, 2009) with many studies concluding this observation is intuitive and as expected (Kordjamshidi, 2011;Raisbeck and Wardlaw, 2009;Stein and Meier, 2000;Willrath, 1996;Zmeureanu et al, 1999).…”
Section: Introductionmentioning
confidence: 76%
“…EERs are one of a range of measures that aim to ensure people are continually reminded of the potential environmental damage due to the poor design of buildings. Numerous researchers have argued that real change can only be achieved through financial incentives leading to behavioural change (Kriese and Scholz, 2011; Source: US Energy Efficiency Administration (2011) Raisbeck and Wardlaw, 2009;West et al, 2010). Final energy use of major sectors within Australia is shown in Figure 4.…”
Section: Energy Efficiency Ratingmentioning
confidence: 99%
“…The literature also indicates that environmental awareness may not be a sufficient argument to motivate making more environmentally-friendly decisions (Raisbeck and Wardlaw, 2009). The research suggested that neither arguments about more individual aspects like ''improved livability,'' ''cost savings'' or ''other people's opinion,'' nor arguments of greater scale, such as ''concern for future generations'' can be considered significant enough to motivate investing in the construction of sustainable houses.…”
Section: Introductionmentioning
confidence: 95%